Construcción de la identidad en la diversidad a través del diálogo interreligioso: El Seminario de Formación Teológica de Puerto Iguazú - Setton, Eli Damian (2007)
The paper analyzes the identity- construction processes which take place in the Seminaries of Theological Formation in Argentine, focalizing at the tensions between the ideal of self and, in the other hand, the partial realization of that ideal. In the relationship with the religious “other”, the socials actors have the experience of their own prejudices. This kind of experience is a part of the identity- construction processes, and the social actor must negotiate this part with the ideal of self. In 2005, the Seminary took place in the tri-border area of Argentina. This area has been considered as a terrorist organization’s refuge. The paper analyzes the tension between this external look and the other look, expressed in the Seminary, of the people who live there.